Intensive cognitive therapy for post-traumatic stress disorder in routine clinical practice: A matched comparison audit - Murray, H; El-Leithy, S; Billings, J (Wiley, 2017)
Objectives: Intensive cognitive therapy for post-traumatic stress disorder (PTSD) has been shown to be as effective as weekly treatment in controlled trials. In this study, outcome data comparing standard and intensive treatments delivered in routine clinical practice were analysed. Methods: A consecutive case series of intensive treatment cases were compared to matched control cases who had completed weekly treatment. Results: Both groups showed significant improvements on PTSD and depression measures. The intensive group showed larger PTSD symptomatic improvement. There were differences between the groups in age and time since trauma, suggesting selection biases in who is offered, and/or who chooses intensive treatment. Conclusions: For some individuals, an intensive format may be more effective than weekly treatment.